Doors datasets - Namoano, Bernadin; Starr, Andrew; Emmanouilidis, Christos; Ruiz Carcel, Cristobal (Cranfield University, 2020)
Data represents urban train condition monitoring raw data. Data contains, current and door motions during opening and closing periods.
Keywords: 'Door Motion'; 'door-opening'; 'Precision Engineering'; 'Automotive Combustion and Fuel Engineering (incl. Alternative/Renewable Fuels)'; 'Engineering Practice'; 'Transport Engineering'